New Approach of the Playfair's Cipher with A Numerical Value of the Keyword - Assia Merzoug; Adda Ali-Pacha; Naima Hadj-Said (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
At least during the last five years there has been an explosion of a public academic research in cryptography for Playfair's cipher. We were interested, and we have proposed a method to improve it, to make it safer and more efficient. We have oversized this encryption matrix by 7x7 coefficents and for its filling, we have combined two chaotic maps (the attractor Henon and logistics map). The attractor Henon of dimension 2, determines the intersection of the row and column of the new matrix playfair. The coefficients of this matrix are calculated from logistic map, each value is a single character of the alphabet used. The secret keyword is formed by the initial conditions of the chaotic attractors.